2022
DOI: 10.3389/fcell.2022.868592
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Repressive Complexes: Shaping Pancreatic Beta-Cell Destiny in Development and Metabolic Disease

Abstract: Pancreatic beta-cells secrete the hormone insulin, which is essential for the regulation of systemic glucose homeostasis. Insufficiency of insulin due to loss of functional beta-cells results in diabetes. Epigenetic mechanisms orchestrate the stage-specific transcriptional programs that guide the differentiation, functional maturation, growth, and adaptation of beta-cells in response to growth and metabolic signals throughout life. Primary among these mechanisms is regulation by the Polycomb Repressive Complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Studies have shown that the dysregulation of epigenetic mechanisms mediated by PRCs is a hallmark of β-cell failure in diabetes. Moreover, the dysregulation of PRC contributes to transcriptional changes associated with β-cell dysfunction in T2D [ 47 , 48 ]. These reports suggest that variants in these genes could impact T2D development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the dysregulation of epigenetic mechanisms mediated by PRCs is a hallmark of β-cell failure in diabetes. Moreover, the dysregulation of PRC contributes to transcriptional changes associated with β-cell dysfunction in T2D [ 47 , 48 ]. These reports suggest that variants in these genes could impact T2D development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by an age-related increase in binding of the Trithorax complex containing Mll1 and JmjD3 which mark the chromatin with activating histone modifications, leading to p16 accumulation ( 44 ). The epigenetic control of p16 is driven by age-related changes in growth-factor signaling pathways ( 45 ). Platelet-derived Growth Factor (PDGF) signaling, which is essential for Ezh2 expression, declines with aging ( 46 ).…”
Section: Senescence In Pancreatic Beta-cells – In Health and Diseasementioning
confidence: 99%
“…Histone modi cations have been shown to be involved in beta cell differentiation, identity, function and proliferation (35)(36)(37)(38). Moreover, evidence suggests that epigenetic mechanisms may be involved in the pathogenesis of diabetes (38)(39)(40)(41). Polycomb dependent histone methylation events have been implicated in beta cell dedifferentiation in both mouse and human beta cell dysfunction resulting in increased expression of genes associated with immature beta cell phenotype and a decrease in expression of genes associated with mature beta cells (38).…”
Section: Introductionmentioning
confidence: 99%